Forming trust in mobile ad -hoc network - Abu Bakar A.; Ismail R.; Jais J.; Abdul Manan J.-L. (2023)
Mobile ad-hoc network which is constructed via mobile nodes without the pre-registration of nodes have created problem in resource sharing. As nodes can join/leave the network randomly therefore nodes may not aware to which nodes is it connected with and this make resources been shared among anonymous nodes which can be trusted/not trusted. This has created unfavorable situation for private transaction. Hence a mechanism to formalize trustworthiness among these anonymous nodes is needed to make sure resources are shared among trusted nodes only. In this paper, we proposed a schema that can compute trust value among anonymous nodes. The schema is formed via direct and indirect approach. Parameters such as recommendation, reputation, knowledge, observation and context were used to evaluate the trust value. The result obtained from the calculation is then mapped with the access privileges to determine the action required. 2009 IEEE.